The correlation between students’ listening to English song habit and grammar mastery - Putri, Anisa Hersa; Sujarwati, Iis (Kajian Pendidikan, Seni, Budaya, Sosial dan Lingkungan, 2024)
Grammar is one of the keys to learning a language and is not easy to do. Meanwhile, factors that influence English Learning do not only come from the teacher, but also from the students’ attitudes. One habit that can be a consideration in helping students master grammar is listening to English songs. The objective of this study was to determine if there is a relationship between students' habit of listening to English songs and their grammar mastery. This research was carried out at SMA Negeri 6 Kota Bengkulu, which was conducted on the twelfth-grade students of SMA Negeri 6 Kota Bengkulu involving 31 students in the academic year 2021/2022. The instruments of this research were a questionnaire on listening habits and a grammar test. Research findings showed that the students had high intensity on listening to English songs also became one of their habits. On the other side, the grammar mastery of the students on average was categorized as low. Only a few students were considered to be high level in grammar mastery. Furthermore, the Pearson Product Moment correlation test revealed no connection between listening to English songs habits and grammar mastery.